Production of Genetically Improved Farmed Tilapia (GIFT) strain of Nile Tilapia (Oreochromis niloticus), Growth Line, Generation 19 (G19) in Malaysia - Mahmuddin, Mahirah; Hamilton, Matthew; Izadi, Fariba (2024)
Production data for 63 families of the GIFT Growth Line, Generation 19 (G19). Data included the Identifiers, list of parents ID, after spawned weight in grams, fry date to date of transfer to nursing tank and spawning date.